One-Loop Helicity Amplitude For Light-By-Light Scattering (Journal of Pharmaceutical Negative Results, 2023)
In this paper, we will aim to calculate analytically the one-loop helicity scattering amplitude and differential cross section for the process γγ→ γγ . The computation of this process takes into account non-zero mass of loop-fermion. In certain kinematic limits, compact analytic expressions exist and can be quickly obtained. We present the covariant and helicity amplitudes for this process